KAJIAN LANSKAP KAWASAN PESISIR WANOKAKA DI DESA WEIHURA KOTA WAIKABUBAK, NUSA TENGGARA TIMUR - Talu, Timotius Tuangu; Setyabudi, Irawan; Hamzah, Amir (Universitas Tribhuwana Tunggadewi, 2019)
Indonesia is an archipelagic country that has abundant tourism potential. One of the tourism commodities in Indonesia is coastal tourism. Wanokaka Beach, located in Waihura Village, Wanokaka Subdistrict, West Sumba Regency has high tourism potential, which is a distinctive visual landscape, cultural objects and attractions of the local community which are the biggest and popular attractions in Sumba culture, namely the attraction of Pasola culture sea worms). From the above explanation, it is necessary to study so that tourism development does not lie behind the existing culture. In this study aims to identify or assess the coastal landscape of Wanokaka and find out the potential and constraints that exist in the Wanokaka Coast which can be developed as a tourist attraction. The approach of this research is descriptive qualitative conducted by observing directly and interviewing to find out the state of the coastal landscape and the activities of the community around the coast of the Wanokaka. The results of the research can be summarized in the form of conclusions or in writing back in writing about the condition of the landscape and the lives of the community, especially in the social and cultural fields. For the results of his research addressing Wanokaka beach has excellent landscape potential that must be developed such as the authenticity of nature with views and cultural tourist attractions that can add to the attractiveness of tourists. This ritual is expressed in the form of ritual Pasola (javelin throwing) and Nyale (sea worm harvest) which are held every year. behind the very strong potential and typical of Wanokaka beach there are obstacles that must be overcome such as accessibility, affordability of electricity, water, telecommunications and lack of community participation and government attention in developing existing potential. Indonesia merupakan Negara kepulauan yang memiliki potensi wisata yang sangat melimpah. Salah satu komoditi pariwisata adalah wisata pesisir (coastal turism). Pantai Wanokaka yang berlokasi di Desa Waihura Kecamatan Wanokaka Kabupaten Sumba Barat memiliki potensi wisata yang tinggi yakni visual lanskap yang khas, objek dan atraksi budaya masyarakat lokal yang merupakan atraksi terbesar dan populer dalam budaya sumba yakni atraksi budaya Pasola (lempar lembing) dan Nyale (panen cacing laut). Dari penjabaran diatas maka perlu adanya kajian agar pengembangan wisata tidak bertolak belakan dengan budaya yang ada. Dalam penelitian ini bertujuan untuk mengidentifikasi atau mengkaji lanskap pesisir pantai Wanokaka serta mengetahui potensi dan kendala yang ada di Pesisir Wanokaka yang dapat dikembangkan sebagai obyek wisata. Pendekatan penelitian ini yakni deskriptif kualitatif dilakukan dengan cara mengamati secara langsung dan wawancara untuk mengetahui keadaan lanskap pantai maupun aktivitas masyarakat di sekitar pesisir wanokaka. Dari hasil penelitian dapat di simpulankan berupa kesimpulan atau melarsirkan kembali secara tertulis mengenai kondisi lanskap dan kehidupan masyarakat terlebih khusus dibidang sosial dan budaya. Untuk hasil penelitiannya menujukan pantai Wanokaka memiliki potensi lanskap yang sangat baik yang harus dikembangkan seperti keaslian alam dengan view serta atraksi wisata budaya yang dapat menambah daya tarik wisatawan. Ritual ini diekspresikan dalam bentuk ritual Pasola (lempar lembing) dan Nyale (panen cacing laut) yang diadakan setiap tahun. dibalik potensi yang sangat kuat dan khas pantai wanokaka terdapat kendala yang harus diatasi seperti aksebilitas, keterjangkauan listrik, air, telekomunikasi serta kurangnya partisipasi masyarakat dan perhatian pemerintah dalam mengembangkan potensi yang ada.